ANALISIS PEMBELAJARAN DISIPLIN MAHASISWA BARU TAHUN AKADEMIK 2020 FKIP UNTAN DI PONTIANAK - Priyo Saptomo (Jurnal Visi Ilmu Pendidikan, 2022)
AbstractThis research is entitled "Analysis of New Student Discipline Learning for Academic Year 2020 FKIP Untan in Pontianak". The formulation of the problem in this research is How Discipline Learning for New Students in the 2020 Academic Year of FKIP Untan in Pontianak. The method used is descriptive method. The form of research is descriptive qualitative. Data collection techniques in this study were: direct communication with data collection tools, interview guides, direct observation using observation sheet data collection tools, documentary studies using data file data collection tools. The results of the study are as follows: Based on research that has been conducted on FKIP Untan students, it is known that there is no difference in learning traffic discipline based on attitudes towards the police (FA). This can be seen from the results obtained, where FA got a value of 1.705 with a p value of 0.186 (p> 0.05). When viewed based on the categorization of variable values, positive values with a score range of 75 get a result of 14% with a frequency of 7 men and 10 women. On a neutral value with a score range of 50-74 get 81% results with the same frequency between men and women as many as 49 people. Meanwhile, the negative categorization got a result of 5% with the frequency of 4 men and 2 women. Keyword : Analysis of student discipline learning.